P1-S2.60 Prevalence and correlates of giving or receiving sex for money, drugs or goods among men who have sex with men in Vancouver, British Columbia. (10th July 2011) - Michelow, W; Hogg, R; Moore, D; Gustafson, R; Trussler, T; McGuire, M; Gilbert, M; ,
Abstract : Background: The exchange of sex for money, drugs, goods/services (transactional sex) is a recognised risk factor for HIV infection, particularly among men who have sex with men (MSM). We investigated the prevalence and correlates of transactional sex among MSM recruited into the Vancouver component of the Public Health Agency of Canada's M-Track second generation national surveillance system of MSM (ManCount). Methods: In 2008−2009, ManCount recruited MSM aged ≥19 years through community venues and events catering to MSM to complete a self-administered questionnaire and provide a blood sample for testing for HIV. We examined responses to questions on having given or received money, drugs or goods/services in exchange for sex in the past 6 months (P6M) and used multivariate logistic regression to explore association of seeking and providing transactional sex with a number of recognised HIV risk factors. The complete dataset included MSM recruited from a drop-in centre for male sex workers (MSW)—we first compared these men to the rest of the sample and then, to reduce confounding, these data were excluded from our detailed analysis of correlates. Results: Of the 1169 participants, 1130 answered the transactional sex questions and 38 were MSW. Of the MSW, 81% reported transactional sex P6M. The MSW differed significantly from the other MSM and were predominantly not gay-identified; reported lower income and education; higher injection drug use, drug use with sex and public sex (all p<0.0001). Of the 1131 participants included in the remaining analysis, 1093 answered the transactional sex questions, with 188 (17.2%) reporting exchanging some consideration for sex P6M—12.0% having received consideration, 10.9% having given, and 5.2% both. 8.7% received money, 7.0% drugs and 4.8% goods; 6.8% gave money, 4.3% gave drugs and 4.6% gave goods. Abstract P1-S2.60 table 1 shows correlates of receiving and giving transactional sex. Conclusion: The exchange of money, drugs or goods/services for sex is common among MSM in ManCount and may be more prevalent in MSM culture than previously thought. Lower income, non-gay identity and more sex partners were associated with receiving consideration for sex, whereas older age, IDU P6M, seeking sex in public places and risky sex were associated with giving consideration. Transactional sex was strongly associated with use of recreational drugs along with sex and emphasises an intimate connection between drug use and sex in the production of HIV risk.